The Ethnoliteracy-Based Guided Discovery Learning Model in Writing Imaginary Story at Elementary Schools - Nurani, Riga Zahara; Sunendar, Dadang; Cahyani, Isah; Rakhmat, Cece (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims at developing an Ethnoliteracy-based guided discovery learning model in writing imaginary stories at elementary schools. It used the research and development (R&D) method with 4D (Define, Design, Develop, and Disseminate) model. Teachers and students in 5th-grade elementary schools served as the subjects of this research. The instruments that this research used included observation, interviews, and documentation with the developed steps of guided discovery learning model consisting of stimulus, problem identification, data collection, data processing, publication, and reflection. The data in this research were analyzed qualitatively and quantitatively. The research found that based on expert assessment, the feasibility of this learning model was scored 87.5% by the linguist and 93.3% by the culture expert. Based on the development trial result, the prepared learning planning was classified as highly practical at 86.7% and practical at 13.3%. In practice, students managed to write an imaginary story and scored an average of 80.28. This means that the Ethnoliteracy-based guided discovery learning model in writing imaginary stories was feasible for use in elementary school students.